Accurate identification of clinically important Acinetobacter spp.: an update - Vijayakumar, Saranya (Future Sci OA, 2019)
Acinetobacter species have emerged as one of the most clinically important pathogens. The phenotypic techniques which are currently available are insufficient in accurately identifying and differentiating the closely related and clinically important Acinetobacter species. Here, we discuss the advantages and limitations of the conventional phenotypic methods, automated identification systems, molecular methods and MALDI-TOF in the precise identification and differentiation of Acinetobacter species. More specifically, several species of this genus are increasingly reported to be of high clinical importance. Molecular characterization such as of bla(OXA-51)-like PCR together with rpoB sequencing has high discriminatory power over the conventional methods for Acinetobacter species identification, especially within the Acinetobacter calcoaceticus–Acinetobacter baumannii complex.